Corporate governance and dividend policy in Poland - Oskar Kowalewski; Ivan Stetsyuk; Oleksandr Talavera (Deutsches Institut für Wirtschaftsforschung (DIW), 2007)
This study examines the relation between corporate governance practices measured by Transparency Disclosure Index (TDI) and dividend policy in Poland. Our empirical approach, constructs measures of the quality of the corporate governance for 110 non-financial companies listed on Warsaw Stock Exchange between 1998 and 2004. We find evidence that an increase in the TDI or its subindices leads to an increase in the dividend-to-cash-flow ratio. These results support the hypothesis that companies with weak shareholder rights pay dividends less generously than do firms with high corporate governance standards. Therefore, minority shareholders often use power to extract dividends. We also find that large and more profitable companies have a higher dividend payout ratio, while riskier and more indebted firms prefer to pay lower dividends.
Keywords: G30; G32; G35; 330; corporate governance; dividend policy; agency theory; Corporate Governance; Dividende; Eigentümerstruktur; Agency Theory; Polen